Morphological and physiological changes induced by Achyranthes aspera-mediated silver nanocomposites in Aedes aegypti larvae - Sharma, Aarti; Mishra, Monika; Dagar, Vinay Singh; Kumar, Sarita (Frontiers in Physiology, 2022)
Aedes aegypti is responsible for the global spread of several ailments like Chikungunya, dengue, yellow fever and Zika. Use of synthetic chemicals is the primary intervention in mosquito management. However, their excessive utilization resulting in spread of toxic ingredients in the environment and threat to beneficial organisms has recommended use of biologically synthesized nanocomposites as a promising approach for vector control. The silver nanocomposites were synthesized using leaf (AL-AgNCs) and stem (AS-AgNCs) extracts of Achyranthes aspera. The early fourth instars of Ae. aegypti were exposed to lethal doses of these nanocomposites to evaluate their effects on the larval development, behaviour, morphology, and midgut histoarchitecture. The cellular damage and deposition of nanocomposites residues in the mid gut was studied using Light and Transmission Electron Microscopy. The A. aspera silver nanocomposites (AA-AgNCs)-exposed larvae exhibited showed dose-dependent extended duration of development and diminished adult emergence; but did not exhibit modified behaviour. An intense damage to the cuticle membrane and slight contraction in internal membrane of anal papillae was noticed. Morphologically, the midgut appeared disorganized, darkly pigmented and shrunk. Histological investigations of the midgut revealed significantly disordered internal architecture with lysed cells, damaged peritrophic membrane and microvilli, disintegrated epithelial layer as well as ruptured and displaced basement membrane. Visualization of the larval midgut through TEM showed severe cellular damage and aggregation of black spots indicating deposition of silver particles released by AA-AgNCs. The investigations revealed the bio-efficacy of A. aspera-mediated AgNCs against Ae. aegypti inducing stomach and contact toxicity in the larvae. The utilization of AA-AgNCs is recommended for Ae. aegypti management as a safe and effective intervention.